ANALISIS FINANCIAL DISTRESS PERUSAHAAN SUB SEKTOR PLASTIK DAN KEMASAN - Guntoro Ilyas; Miftahul Hadi (Media Mahardhika, 2020)
This research aims to find out the financial performance of plastics and packaging sub-sector companies in the period 2016-2018. This research uses secondary data on plastic and packaging sub-sector companies listed on the Indonesia Stock Exchange using comparative descriptive analysis techniques. This study uses model analysis or Zmijewski method. The study found that of the ten companies analyzed, nine companies showed financial performance classified as healthy or not potentially bankrupt, although two of them needed more attention because the results showed a decrease in financial performance while one company showed unhealthy financial performance.